2005
DOI: 10.1029/2005gl023728
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of daytime mesopause temperatures obtained using unique ground based optical and meteor wind radar techniques over the magnetic equator

Abstract: This paper presents the first ever comparison of daytime Mesopause OH rotational temperatures as determined using Meinel (8‐3) dayglow emissions with those obtained using the recently established and collocated, meteor radar (SKiYMET) over the magnetic equator in India. The measurements were made over Thiruvananthapuram (8.5°N, 76.5°E, 0.5°N diplat.) for January–May 2005 period. Overall agreement had been good (±20 K) with all the gross features coming out fairly well. Further, the temperatures estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
(35 reference statements)
0
31
0
Order By: Relevance
“…The daytime OH emission intensity measurements were used to estimate the mesopause temperature. These mesopause temperatures have already been compared and validated (Vineeth et al, 2005). Trivandrum, being a tropical station, the dayglow measurements are largely restricted to the clear sky conditions.…”
Section: Experimental Database and Methods Of Analysismentioning
confidence: 99%
“…The daytime OH emission intensity measurements were used to estimate the mesopause temperature. These mesopause temperatures have already been compared and validated (Vineeth et al, 2005). Trivandrum, being a tropical station, the dayglow measurements are largely restricted to the clear sky conditions.…”
Section: Experimental Database and Methods Of Analysismentioning
confidence: 99%
“…The characteristics of the photometer and data analysis procedure had been published elsewhere (Sridharan et al, 1999). The measurements have already been validated/compared with the in situ WINDII satellite measured temperature and also collocated meteor radar measured temperature in the Indian region (Vineeth et al, 2005, and references therein). It has been found that the temperatures measured, using the aforementioned techniques, agree very well (within ±20 K) with each other with all the variability coming out fairly well.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the ground-based spectro/photometry of specific atmospheric emissions during both day and nighttime, has enabled measurement/estimation of key parameters representing the mesopause (e.g., the mesopause temperature) (e.g., Taylor et al, 2001;Vineeth et al, 2005, and references therein). In this context, the unique Multi-Wavelength Dayglow Photometer (MWDPM) developed in India had been successfully used for making daytime mesopause temperature measurements over the Indian longitudes in recent years (Sridharan et al, 1999;Pant et al, 2007;Vineeth et al, 2005). Presently, this dayglow photometer is operated from Trivandrum (8.5 • N; 77 • E; dip lat.…”
Section: Introductionmentioning
confidence: 99%
“…The MWDPM is a unique instrument which can measure daytime intensities of three different wavelengths nearly simultaneously (Sridharan et al, 1998;Vineeth et al, 2005 and references therein). Daytime OH rotational temperatures were estimated by the selection of two wavelengths, 731.6 and 740.2 nm (Meinel 8-3 band).…”
Section: Methodsmentioning
confidence: 99%
“…However, ground-based Lidars and spectrometers from different locations over the globe have also enabled measurements of upper atmospheric temperatures and its temporal variabilities (Taylor et al, 2001;She et al, 2003;French and Burns, 2004). In terms of equatorial mesospheric energetics, recent observations using meteor wind radar and the unique multi-wavelength dayglow photometer (MWDPM) has already produced some interesting results (Sridharan et al, 1999;Pant et al, 2004;Vineeth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%